(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
In this study, a metal-free carbon nitride (CN) was investigated for the first time as a potential fluorescence sensor for detection of nitrate ions (NO3-). The CN was prepared through thermal polymerization of urea precursor at 823 K and characterized by diffuse reflectance ultraviolet-visible (DR UV-Vis), Fourier transform infrared (FTIR), and fluorescence spectroscopies. The DR UV-Vis spectrum confirmed that CN could absorb light up to 450 nm. On the other hand, the FTIR spectrum revealed the presence of graphitic CN single and double bond characters in the 800-1700 cm-1 region. From the fluorescence spectroscopy, three excitation peaks at 278, 310 and 369 nm were observed due to the presence of N=C, C=O and N-C groups, respectively. The fluorescence sensor capability of the CN was then investigated using concentrations of NO3- in the range of 300-1800 mM. It was confirmed that the intensities of the emission sites were quenched linearly with the concentrations of the NO3-. The CN showed good reproducibility with relative standard deviation (RSD) values were 1.5-7.2%. Â These results suggested that CN can act as the fluorescence sensor for NO3-.